Water, water : [poems] - Collins, Billy (Random House, 2024)
"In more than sixty new poems, Billy Collins writes with joy and wonder about the beauty and irony of daily life. The best poetry, he believes, begins with clarity and ends in mystery, and in Water, Water we encounter a writer endlessly astonished by the world all around. Turning his eye to the cat drinking from the swimming pool or the nurse calling your name in the waiting room or the astronaut reading Emily Dickinson while orbiting earth, Collins captures images and moments that mean so much more than they might initially seem. With a voice both simple and melodic, hospitable and lyrical, the poetry of Billy Collins asks each of us to slow down and notice the commonplace in order to discover the sublime. No wonder The New York Times and The Wall Street Journal both call him one of America's favorite poets"--